2021
DOI: 10.1088/1755-1315/761/1/012096
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of treatment with newly developed probiotic versus phaleria macrocarpa leaves extract on the histological features in immunocompromised New Zealand white rabbits

Abstract: This research aimed to examine the possible effectiveness of treatment with a freshly formulated new probiotic versus Phaleria macrocarpa leaves extract indicated by the histopathological changes occurred to the colon of the immunocompromised New Zealand White (NZW) rabbits. The study included 40 rabbits, divided into 4 groups. Three of the groups were fed with the immunosuppressive medication (azathioprine, 500 mg/kg/day) to be immunocompromised, Group B was treated with P. macrocarpa extract, Group Ctreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In comparison to the formulated probiotic or non-treated groups, treatment with P. macrocarpa leaves methanol extract (500 mg/kg) resulted in a remarkable recovery in the colon tissues of immunocompromised New Zealand rabbits based on the observed histopathological changes ( Saleh et al, 2021 ). Samples of the immunocompromised rabbits treated with P. macrocarpa extract showed a distinct decrease in mucin secretion and goblet cell structured composition, as well as a significant recovery in body weight gain, physical activity, a reduction in pro-inflammatory immune markers, and abundant rates of neutrophils in plasma ( Saleh et al, 2021 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In comparison to the formulated probiotic or non-treated groups, treatment with P. macrocarpa leaves methanol extract (500 mg/kg) resulted in a remarkable recovery in the colon tissues of immunocompromised New Zealand rabbits based on the observed histopathological changes ( Saleh et al, 2021 ). Samples of the immunocompromised rabbits treated with P. macrocarpa extract showed a distinct decrease in mucin secretion and goblet cell structured composition, as well as a significant recovery in body weight gain, physical activity, a reduction in pro-inflammatory immune markers, and abundant rates of neutrophils in plasma ( Saleh et al, 2021 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Colitis induction in New Zealand rabbits via DSS treatment enables the monitoring of disease progression, from acute inflammation to chronic fibrosis [ 62 ]. Furthermore, studies have reported on the therapeutic effects and mechanisms of microorganisms and plant extracts in TNBS-induced rabbit colitis [ 63 , 64 ]. If endoscopic biopsy is required, the New Zealand rabbit IBD model is the recommended choice.…”
Section: Non-rodent Models In Mammalsmentioning
confidence: 99%